Suspected Deep Interaction and Triggering Between Giant Earthquakes in the Chilean Subduction Zone. Issue 11 (14th June 2018) - Bouchon, Michel; Marsan, David; Jara, Jorge; Socquet, Anne; Campillo, Michel; Perfettini, Hugo
Abstract: Between 2010 and 2015 three giant earthquakes occurred in the Chilean subduction where the oceanic Nazca plate plunges under South America. These were the largest events there since the gigantic M 9.5 1960 earthquake so their close occurrences raise the question of a possible link between them. We show here that two‐and‐a‐half days after the M 8.2 Iquique earthquake, seismic activity started to increase downdip below (depth 100 km) the future Illapel epicenter. This increase, which began with the largest intermediate‐depth earthquake in the Chilean subduction after Iquique, lasted until the M 8.3 Illapel earthquake, 18 months later. The mechanisms involved suggest that the Iquique earthquake started a tear in the slab directly downdip from the future epicenter. This study relies on seismicity which occurs in the cold core of the slab and which is the only direct information we have on processes occurring at these depths. The results support that giant earthquakes interact at the scale of a subducting plate and suggest that this interaction occurs through the deep slab. Plain Language Summary: Our study shows that giant earthquakes interact and can trigger one another at the scale of a subducting plate. Studying the evolution of seismic activity in the deep ( 100 km) slab, which is the only tool we presently have to investigate physical processes taking place at these depths, we show that, accompanying a giant earthquake, the slab deforms to large depth and far distances, something unthought of before. This paper is able to trace the path which links two recent major earthquakes in the Chilean subduction, the M 8.2 2014 Iquique and the M 8.3 2015 Illapel earthquake. We show that the first event produced a tear in the deep slab 1, 200 km away, directly downdip from the second event epicenter. We show how this tear expanded with time for 18 months and finally spread to the seismogenic zone and the future epicentral area 2 months before the second megathrust. These results support that most large subduction earthquakes are not spontaneous ruptures but are preceded by the slow deformation/slip of the plates below the seismogenic zone, which is a very encouraging result for the future. Key Points: Seismic analysis shows how an earthquake triggered a tear in the slab 1, 200 km away which led to another major earthquake 18 months later The 2015 M 8.3 Illapel (Chile) earthquake was preceded by the deformation of the slab below the future rupture zone Large earthquakes interact in the Chilean subduction